(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
This paper aims to address, from a legal analysis, the situation that arises between registered trademarks and the limitations imposed by domestic legislation, as long as the latter can be considered as an unjustified interference in relation to rights trade or imply a redefinition of the protection of trademarks. For this, the precedents of Canada, Australia and the European Union will be analyzed, in order to determine to what extent they could influence Argentina and its legislation. First, the impact of tobacco / cigarette packaging and the FCTC / FCTC will be analyzed. Next, we will continue with the jurisprudence analysis of the Australian Court, which meant a necessary precedent for European Union legislation and jurisprudence. Finally, the article will focus on the possible impact that both the FCTC / FCTC and the leading cases of Australia and the EU may have on Argentina and to what extent the country took action in this regard.